Anti-Angiogenic Agent Combined with Anti-PD-1 Immunotherapy Showed Activity in Patients With Classical Hodgkin Lymphoma Who Have Failed Immunotherapy: A Retrospective Case Report Study - Yan, Zheng; Ma, Jialin; Yao, Shuna; Yao, Zhihua; Wang, Haiying; Chu, Junfeng; Zhao, Shuang; Liu, Yanyan (Frontiers in Immunology, 2021)
Background: PD-1/PD-L1 inhibitor immunotherapy has showed impressive activity in various cancers, especially relapsed/refractory (r/r) classical Hodgkin lymphoma (cHL). However, acquired resistance is inevitable for most patients. Sometimes severe side effects also lead to treatment termination. When immunotherapy failed, alternative treatment options are limited. In the past few years, we have used the anti-angiogenic agent apatinib and PD-1 inhibitor camrelizumab to treat cHL patients who failed prior immunotherapy. In this study, we analyzed the data of these patients. Patients and methods: Patients with r/r cHL who had failed immunotherapy and subsequently received apatinib-camrelizumab (AC) combination therapy were included in this study. Patient data were collected from medical records and follow-up system. The efficacy and safety of AC therapy were analyzed. Results: Seven patients who failed immunotherapy were identified in our database, of which five patients acquired immunotherapy resistance and two patients experienced severe side effects. They received a combination of camrelizumab (200 mg every four weeks) and apatinib (425 mg or 250 mg per day). As of the cut-off date, these patients had received a median of 4 cycles (range, 2 - 31) of treatment. Two (2/7) patients achieved complete response, four (4/7) partial response, and one (1/7) stable disease. The median progression-free survival was 10.0 months (range, 2.0 – 27.8). Low-dose apatinib (250 mg) plus camrelizumab was well tolerated and had no unexpected side effects. Besides, no reactive cutaneous capillary endothelial proliferation was observed in AC-treated patients. Conclusions: Low dose apatinib plus camrelizumab might be a promising treatment option for r/r cHL patients who have failed immunotherapy. This combination treatment is worthy of further investigation in more patients including solid cancer patients who have failed immunotherapy.